Circulatory titin and miR-451a are possible sarcopenia biomarkers in elderly people - Mancuso, Roberta; Citterio, Lorenzo Agostino; Agostini, Simone; Miglioli, Rossella; Nuzzi, Riccardo; Antolini, Laura; Trecate, Fabio; Clerici, Mario (Frontiers in Aging, 2025)
IntroductionSarcopenia is a clinical syndrome characterized by decline of muscle mass, strength or physical performance that occur with advancing age. Diagnosis is currently based on assessment of muscle mass and performance. New biomarkers are needed in clinical practice for diagnosis, monitoring and treatment of sarcopenia. The measurement in urine of titin (TTN), a muscular protein essential for structure and function of sarcomere, has been recently suggested as useful biomarker for the diagnosis of sarcopenia. The titin N-terminal fragment (N-TTN), produced by proteolysis during muscle damage, is released in the bloodstream and is secreted in the urine, and it was suggested as indicator of muscle injury. The primary aim of our study is to evaluate the potential of serum TTN and N-TTN expression as biomarker of sarcopenia, an aspect that has not been the subject of much research so far. Additionally, the secondary aim is to explore possible relationship between the serum expression of titin and miR-451a, its possible miRNA regulator.MethodsWe verified serum TTN, N-TTN and miR-451a concentration in a cohort of 70 sarcopenic patients who were undergoing rehabilitation; results were compared to those obtained in 90 age- and sex-matched healthy controls (HC).ResultsResults showed that TTN and N-terminal TTN (N-TTN) (p < 0.0005 for both) and miR-451a (p < 0.0001) were significantly upregulated in serum of patients compared to HC. Rehabilitation significantly reduced TTN and N-TTN expression (p < 0.05 for all), while induced a significant increase in miR-451a expression (p = 0.008); ROC analysis showed that the change of miR-451a may be a predictive biomarker for rehabilitation outcome (p = 0.0198).DiscussionThis study suggests the involvement of TTN, N-TTN and miR-451a in sarcopenia; moreover, the monitoring of miR-451a concentration may be useful proxy to measure the effectiveness of rehabilitation intervention.